If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 1(4) = 3 Multiply 1 * 4 1x + 4 = 3 Reorder the terms: 4 + 1x = 3 Solving 4 + 1x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 1x = 3 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 3 + -4 1x = 3 + -4 Combine like terms: 3 + -4 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| w(4w)=144 | | w(w-4)=144 | | w(4-w)=144 | | 12(0.25)= | | 3g+9-g=17 | | w(w+4)=144 | | 4x^2=-16x-9 | | 8x^2-15x-x^3=0 | | -6(x-9)+3= | | -8x=128 | | 4s-4g=5g | | 2x-10=3y+9 | | -12.20+-6.01= | | 7-5[4-2y-5]= | | 7x+2+8x=32+5x | | 10+y=11 | | 16x^3+54= | | 0.35x=49 | | y-3=2.5(x+1) | | b^2-2b-8=5 | | 19.21-3.06= | | -0.4=V-5 | | (8a+7c)(8a-7c)= | | -0.4=-5V | | 2a^2-ab-3b^2=0 | | -6p-(3p-4)=2p-7 | | 5a^3b-45ab^3= | | 32-7y=11 | | x+x+1+x+2=3 | | k^2-6k-9=0 | | 144b^2-36=0 | | 7-3x=-4(2+x) |